THE IMAGE OF KAMPUNG BALUWARTI AS A JAVANESE CULTURAL EDU-TOURISM DESTINATION BASED ON THE CULTURE OF SURAKARTA SUNANATE PALACE - Amad Saeroji; Tomi Agfianto; Deria Adi Wijaya; Joko Sadoso Priyo; M Marimin (Jurnal Pengembangan Kota, 2020)
Kampung Baluwarti is a cultural edu-tourism destination in Surakarta City, Central Java, Indonesia. Systematically, this study aims to: 1) identify the characteristics of the tourism products of Kampung Baluwarti; 2) study the development strategies of the image of Kampung Baluwarti as a cultural edu-tourism destination in Surakarta and formulate the cultural education tour packages that are tailored to existing potentials, environment, and regional planning. The research applied a descriptive-qualitative method with PASOLP (Product Analysis of Outdoor Leisure Planning Sequence) which offers a creative, pragmatic, and operational approach to modern tourism area planning. In this case, the research conducted two PASOLP stages: defining the object and attraction and providing recommendations on the needs and priorities. The data collection technique was conducted by collecting the necessary information through interviews with key informants. Field observation carried out the existing condition. Besides, a literature study was used to dig up literary information related to Kampung Baluwarti that was not obtained in interviews and observation. Besides, a literature study was used to explore literary information related to Kampung Baluwarti that was not obtained in interviews and observation. The results show that the tourism products, in this case, have multiple roles: not only for conservation and preservation purposes but also for improving the economy of the local people living in the area. Development strategies that are tailored to product characteristics, local community conditions, and planning are formulated with Javanese traditional tour packages that can form the image of Kampung Baluwarti as a cultural edu-tourism destination in Surakarta. Therefore, cultural edu-tourism destination carries the appropriate concept in developing tourism strategies based on the Javanese culture of Surakarta Sunanate Palace.